Prevalence, Incidence, and Clearance of Human Papillomavirus Types Covered by Current Vaccines in Men With Human Immunodeficiency Virus in the SUN Study. (19th September 2019) - Patel, Pragna; Bush, Tim; Conley, Lois; Unger, Elizabeth R; Darragh, Teresa M; Henry, Keith; Escota, Gerome; Brooks, John T; Kojic, Erna Milunka
Abstract: Background: High-risk anal human papillomavirus (HPV) infection is prevalent among men living with human immunodeficiency virus (HIV); the association between 9-valent (9v) high-risk HPV (HR-HPV) vaccine types and abnormal cytology has not been well characterized. Methods: We followed a prospective cohort study of persons with HIV at 7 HIV clinics in 4 US cities from March 2004 through June 2012. Annually, providers collected separate anal swabs for HPV detection and cytopathologic examination. Among men, we examined prevalence, incidence, and clearance of 9v HR-HPV vaccine types, compared with other HR types, and associations with abnormal cytology to assess potential vaccine impact. Results: Baseline prevalence of any anal 9v HR-HPV type among men who have sex with men (MSM) and men who have sex with women (MSW) was 74% and 25% ( P < .001), respectively. Among 299 MSM, abnormal cytology was detected in 161 (54%) MSM and was associated with the presence of any 9v HR-HPV (relative risk [RR], 1.8 [95% confidence interval CI, 1.3–2.6]; P < .001). Among 61 MSW, abnormal anal cytology was detected in 12 (20%) and was associated with the presence of any 9v HR-HPV (RR, 4.3 [95% CI, 1.6–11.5]; P < .001). Conclusions: Among men with HIV, the prevalence of the 7 HR-HPV types in the 9v vaccine was high and was associated with abnormal cytology. These findings indicate that men with HIV could benefit from prophylactic administration of the 9v HPV vaccine.